Clinical Use of Factor XIII Concentrates - Lassila, Riitta (Seminars in Thrombosis and Hemostasis, 2016)
Factor (F) XIII deficiency is a congenital rare bleeding disorder (RBD), with an estimated prevalence of 1 in 1 to 2 million individuals, and more than 1,200 patients have been diagnosed to date. In newborns, umbilical cord bleeding is typical, and later in life during trauma, surgery and even spontaneously prolonged bleeds, reproduction, and delivery complications occur frequently without appropriate replacement therapy. Also, an acquired form of FXIII deficiency may occur via massive bleeds or neutralizing antibodies. In the inherited form of FXIII deficiency, prophylaxis with FXIII concentrate is administered to prevent the very high risk of intracranial bleeds, the incidence being close to 30%. Laboratory diagnosis of FXIII deficiency is based on measuring plasma FXIII antigen and activity, and it is claimed that FXIII activity of around 5 IU/dL would suffice to protect from bleeds. However, at the low levels of detection, most FXIII methods are inaccurate, and quality controls and collaboration with reference laboratories are important to improve the accuracy of low-level FXIII measurements. The trough target for prophylaxis should be set to 10 to 20 IU/dL, which is achievable by administration of 25 to 35 IU/kg every 4 to 6 weeks. However, general risk factors influencing hemostasis should be carefully evaluated, including anemia and hypertension. Fibrin cross-linking by FXIII is of major importance and red cells bind to fibrin partially via platelets and FXIII to promote clot strength. Physiologically, platelets and macrophages contain FXIII providing cellular support; thus, the patients may benefit from platelet transfusion during problematic bleeds. Plasma-derived and recently a recombinant FXIII concentrate are available; however, the latter has mainly anecdotal data regarding management of bleeds and surgery, and its access is limited due to the high cost. The international registry RBD database, (RBDD) continues to gain cumulative knowledge, and registration of all FXIII deficient patients, both inherited and acquired, is highly recommended.
Keywords: factor XIII; FXIII; bleeding disorders; coagulation